Penyakit Orf Pada Kambing (Studi Kasus di CV Mitra Farm, Bogor, Jawa Barat) - N Kotimah; N Irwani; K Magfiroh (Politeknik Negeri Lampung, 2019)
Goats are livestock that is classified as small ruminants. One of the factors that influence goat productivity is health management. Health management is a disease control process so that livestock productivity can be maximized. One of the goat diseases in CV Mitra Tani Farm is an 'orf' disease.